Vestigios de la liturgia catalano-narbonesa en fuentes hispanas - Rubio Sadia, Juan Pablo (Miscel·lània litúrgica catalana, 2014)
The catalano-narbonese liturgical tradition, formed in the first decades of the 9th century, did not remain circumscribed to the Septimanian and Catalan dioceses and monasteries, but was eventually extended during the 10th and 11th centuries to some other peninsular churches, both close and distant. This article studies the influences of this tradition detected in some roman breviaries and antiphonaries coming from Roda de Isábena, Barbastro, Lleida, Palencia, Oviedo, Pamplona and Tui, by the comparative study of the responsoria de tempore series. It also tries to clarify the historical factors that originated these influences and its relationship with the process of liturgical romanisation in the Hispanic sees.